Trabalho em turnos nas empresas de Botucatu, São Paulo: estudo descritivo Work by shifts in Botucatu, São Paulo: a descriptive study - Miguel Angelo Rosa Martinez; Luiz Roberto de Oliveira (Cadernos de Saúde Pública, 1997)
Em face da inexistência de dados sobre esquema de trabalho em turnos em empresas de Botucatu, solicitaram-se delas informações sobre ramo de atividade, número de funcionários e esquema de trabalho. Às que registraram tal ocorrência, enviou-se um questionário visando à caracterização da forma de organização da jornada de trabalho. Das 66 empresas participantes da pesquisa, 14 referiram a existência de trabalho em turnos, englobando 6.541 funcionários, de um total de 9.502, sendo 2.346 de setores da produção. Nesses setores, os sistemas contínuo alternado e descontínuo permanente predominaram. Em oito empresas os sistemas eram alternados, cinco delas com esquemas apresentando freqüência de revezamento de seis ou mais dias. São descritas outras formas de organização encontradas. Conclui-se que, com o quadro descrito, torna-se possível estudar as relações entre trabalho em turnos, saúde e vida social dos trabalhadores. In view of the lack of information on shift-work schedules and working organization in companies located in Botucatu, São Paulo State, we obtained initial information on areas of economic activity, number of workers, and work schedules from companis by using facsimiles and mailgrams afler receiving a list of companies from the directory of the CIESP. To those who confirmed the use of work in shifts, a questionnaire with instructions was sent in order to characterize how work was organized. There were 42 manufacturing industries among 66 companies responding to the study. Fourteen companies reported occurrence of work in shifts, including 6,541 workers out of 9,502 in the 66 companies. There were 2,346 workers with shift schedules on production divisions in the companies reporting the existence of shift systems. Eight companies had been using rotating shift systems, of which 5 reported rotation schemes with 6 or more consecutive night shifts. Two companies notified shift schedules with counter-clockwise direction of rotation including 684 workers in production divisions. There were systems with single and multiple shifts lasting from 5 to 8 hours and many work schedules even with the same length and same number of shifts. This information will allow us to evaluate the relationship between shift work, health, and the social life of shift workers.